Evaluasi Manajemen Sistem Organisasi Klub Bola Voli GVC Grengeng Kecamatan Karanganyar Kabupaten Kebumen - Ilham Fadhillah, Rangga Maulana; Wijaya, Febri (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
: This study aims to evaluate the management system of the GVC Grenggeng volleyball club organization in Karanganyar District, Kebumen Regency. The evaluation was conducted using the CIPP (Context, Input, Process, Product) model. This study uses a qualitative descriptive approach with a survey method. The study population consisted of athletes, coaches, and club administrators with a sample of 20 people selected using a purposive sampling technique, including 15 athletes, 2 coaches, and 3 administrators. Data collection was carried out through observation, interviews/questionnaires, and documentation studies. The results of the study showed that the context aspect obtained a good category 55%, the input aspect obtained a good category 70%, the process aspect obtained a good category 50%, and the product aspect obtained a good category 50%. Overall, the management system of the GVC Grenggeng volleyball club organization is in the good category, but still needs improvement in several aspects to reach the optimal level. This study provides recommendations for improving the club management system in order to improve the quality of the organization and achievement of achievements.